Legume crop rotation suppressed nitrifying microbial community in a sugarcane cropping soil. Issue 1 (December 2017) - Paungfoo-Lonhienne, Chanyarat; Wang, Weijin; Yeoh, Yun; Halpin, Neil
Abstract Nitrifying microorganisms play an important role in nitrogen (N) cycling in agricultural soils as nitrification leads to accumulation of nitrate (NO3 − ) that is readily lost through leaching and denitrification, particularly in high rainfall regions. Legume crop rotation in sugarcane farming systems can suppress soil pathogens and improve soil health, but its effects on soil nitrifying microorganisms are not well understood. Using shotgun metagenomic sequencing, we investigated the impact of two legume break crops, peanut (Arachis hypogaea ) and soybean (Glycine max ), on the nitrifying communities in a sugarcane cropping soil. Cropping with either legume substantially increased abundances of soil bacteria and archaea and altered the microbial community composition, but did not significantly alter species richness and evenness relative to a bare fallow treatment. The ammonia oxidisers were mostly archaeal rather than bacterial, and were 24–44% less abundant in the legume cropping soils compared to the bare fallow. Furthermore, abundances of the archaealamoA gene encoding ammonia monooxygenase in the soybean and peanut cropping soils were only 30–35% of that in the bare fallow. These results warrant further investigation into the mechanisms driving responses of ammonia oxidising communities and their nitrification capacity in soil during legume cropping.